IDENTIFIKASI TINGKAT KELAYAKAN HUNI PERMUKIMAN DI KELURAHAN DALAM BUGIS BERDASARKAN ASPEK KONDISI JALAN LINGKUNGAN - Inda Purnama; Sulistyarini Sulistyarini; Agus Sugiarto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractKelurahan Dalam Bugis is a light slum category (quite livable). Identification of the level of livability of settlements needs to be done in Kelurahan Dalam Bugis. This study aims to determine the distribution of the level of livability of settlements based on aspects of environmental road conditions. The form of research is descriptive research with qualitative methods. Held in the Kelurahan Dalam Bugis. Methods of data collection by observation, interviews and documentation. Data analysis techniques are data reduction and data presentation. The results of the study describe the distribution of the livability level of the Dalam Bugis Village settlement based on the aspect of environmental road conditions. The distribution of the level of livability of settlements is livable (light slums) and quite livable (light slums). Habitable settlements 3 spaces, light slums 1 109°20'51.84"T to 109°20'50.85"E and 0°1'34.15"S to 0°1'36.53"S. Light slums 2 109°21'1.96"T to 109°21'30.73"E and 0°1'26.24"S to 0°2'1.70"S. Light slums 3 109°21'52.09"E to 109°21'44.90"E and 0°1'54.34"S to 0°1'59.24"S. The total area is 101.47 ha, covering 53% of the Kelurahan Dalam Bugis area with 1,360 settlements. 3 room livable settlement, moderate slum 1 109°20'51.80"T to 109°21'14.47"E and 0°1'23.90"S to 0°1'54.88"S. Moderate slum 2, 109°21'6.62"E to 109°21'8.86"E and 0°1'25.45"S to 0°1'34.97"S. Moderate slum 3, 109°21'37.53"E to 109°21'27.50"E and 0°1'45.40"S to 0°2'9.97"S. The total area is 47% of the area of Kelurahan Dalam Bugis with 2,733 settlements.Keywords: Feasibility Level, Settlement, Slum